2006
DOI: 10.1074/jbc.m600537200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Cleaved Downstream of Caspase Activation in Monocytes Undergoing Macrophage Differentiation

Abstract: We have shown previously that caspases were specifically involved in the differentiation of peripheral blood monocytes into macrophages while not required for monocyte differentiation into dendritic cells. To identify caspase targets in monocytes undergoing macrophagic differentiation, we used the human monocytic leukemic cell line U937, whose macrophagic differentiation induced by exposure to 12-O-tetradecanoylphorbol 13-acetate (TPA) can be prevented by expression of the baculovirus caspase-inhibitory protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 70 publications
(59 reference statements)
3
39
1
1
Order By: Relevance
“…These different data were validated by those obtained with VP16 (Figs. 2C-2F), which is known to activate numerous caspases, including caspase-2 (38), and which are in agreement with previous investigations (39,40). So, taken together, our data strongly support an activation of caspase-2 under treatment with 7KC.…”
Section: Analysis By Conventional Fluorescence Microscopy and Flow Cysupporting
confidence: 93%
“…These different data were validated by those obtained with VP16 (Figs. 2C-2F), which is known to activate numerous caspases, including caspase-2 (38), and which are in agreement with previous investigations (39,40). So, taken together, our data strongly support an activation of caspase-2 under treatment with 7KC.…”
Section: Analysis By Conventional Fluorescence Microscopy and Flow Cysupporting
confidence: 93%
“…8,38,39 Albeit for myeloid cells the involvement of caspases in monocytic differentiation is most evident, 4,5 the functional role of the caspase targets recently identified during differentiation of progenitor cell lines is elusive. 40 Therefore, cleavage of full-length HPK1 in primary myeloid progenitor cells and the generation of a constitutively active HPK1-N kinase provide a possible mechanistic explanation for growth factor-independent survival during monocytic differentiation. Functional analyses of additional caspase targets will probably further improve the understanding of monocytic differentiation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…17 Caspase-8 activates downstream caspase-3 that cleaves a limited number of intracellular proteins. 19 Here, we demonstrate that the synchronized oscillatory activation of PI3K/AKT and ERK1/2 amplifies these signaling pathways and that PI3K/AKT waves end with caspase-8 activation, suggesting that a molecular clock is involved in the control of caspase activity along CSF-1-driven macrophage differentiation.…”
Section: Introductionmentioning
confidence: 94%
“…17 We have shown that CSF-1-mediated differentiation requires the activation of caspase-8 in a multimolecular platform whose formation culminated 2 to 3 days after CSF-1 stimulation. [17][18][19][20] As a consequence, the serine/threonine kinase RIP1 is cleaved, allowing the release of a cleavage fragment involved in the down-regulation of NF-B activity that characterizes terminal macrophage differentiation. 17 Caspase-8 activates downstream caspase-3 that cleaves a limited number of intracellular proteins.…”
Section: Introductionmentioning
confidence: 99%